INTERSEMIOTIC MEANING-MAKING IN MULTIMODAL ACADEMIC WRITING: HOW IMAGES AND WORDS WORK TOGETHER IN EFL PRE-SERVICE TEACHER TEXTS - Irsyad Nugraha; Muhammad Soni; Moch Zidane Maulana; Aryani Nurwasilah; Ichsan Fajar Sidiq (University of Kuningan, 2026)
In contemporary higher education, academic writing increasingly involves the integration of visual and verbal resources, positioning multimodal literacy as a crucial competence for EFL pre-service teachers (Jewitt, 2016; O’Halloran, 2008). Despite growing interest in multimodality, research on EFL academic writing has largely focused on linguistic features, often overlooking intersemiotic relations between images and written language (Royce, 2002; Royce & Bowcher, 2013). Addressing this gap, this study investigates how intersemiotic meaning is constructed in multimodal analytical exposition texts produced by EFL pre-service teachers. Employing a qualitative design with Multimodal Discourse Analysis grounded in Systemic Functional Linguistics (Halliday & Matthiessen, 2013) and intersemiotic complementarity, the study analyzes semantic relations across visual and verbal modes. The findings reveal that declarative mood, balanced modalization, and dominant material processes establish an authoritative and persuasive stance, while visual elements re-realize and extend ideational meanings through representational structures. The study concludes that effective multimodal academic writing depends on strong intersemiotic alignment and highlights the importance of explicitly developing visual–verbal meaning-making competence in EFL teacher education.